1976
DOI: 10.1039/c39760000959
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally easy isomerization of acetylenic alcohols with potassium 3-aminopropylamide. A new, high yield synthesis of functionally differentiated αω-difunctional structures

Abstract: Potassium 3-aminopropylamide, readily prepared in situ from K H and 3-aminopropylamine, effects rapid, multipositional isomerization of the triple bond in prop-2-ynylic and other acetylenic alcohols t o the chain terminus remote from the hydroxy function, within minutes at 0-20 "C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The product was then deprotected using K 2 CO 3 in MeOH to give the target terminal alkyne 20. . 34 Since allenes are known to undergo isomerization to alkynes when treated with strong bases, as in the alkyne zipper reaction, [35][36][37] we decided to continue the synthesis using allene 26.…”
Section: Scheme 3 Preparation Of Vinyl Triflatementioning
confidence: 99%
See 2 more Smart Citations
“…The product was then deprotected using K 2 CO 3 in MeOH to give the target terminal alkyne 20. . 34 Since allenes are known to undergo isomerization to alkynes when treated with strong bases, as in the alkyne zipper reaction, [35][36][37] we decided to continue the synthesis using allene 26.…”
Section: Scheme 3 Preparation Of Vinyl Triflatementioning
confidence: 99%
“…Before trying the isomerization of the allene using standard methods, 35,36 it was decided to investigate if it was possible to form the nine-membered ring compound 29 di-rectly from the allene 19 (Scheme 9). Strong bases are known to induce the isomerization of allenes to terminal alkynes.…”
Section: Scheme 8 Preparation Of Aldehyde 19mentioning
confidence: 99%
See 1 more Smart Citation
“…per reaction 6 before protection of the alcohol of 5 as the tert -butyldimethylsilyl ether (92%). This protecting group is stable to subsequent conditions used to build the diene systems and is removed under nonacidic conditions without isomerization of the double bonds.…”
mentioning
confidence: 99%
“…tive thermodynamic stabilities of the components. The discovery of the ''acetylenic zipper" reacIt has been suggested that in cases where the base tion has widened the scope of base mediated dkyne is the salt of a diamine such as ethylenediamine (4) is~merizations ( 5 , [10][11][12]. Using a very strong or 1,3-diaminopropane (9, the base may be able to base, the potassium salt of 1,3-diaminopropane abstract and donate a proton in a cyclic fashion (DAP) in DAP, the migration of a triple bond more (Scheme 1).…”
mentioning
confidence: 99%